Challenges in implementing the new BASHH guidelines for the management of gonorrhoea. (February 2014) - Rodgers, S; Murgatroyd, M; Perez, K; Kingston, M; Lee, V
Neisseria gonorrhoeae has progressively developed reduced sensitivity to different classes of antibiotics. The British Association for Sexual Health and HIV (BASHH) updated guidelines for the diagnosis and management of gonorrhoea in 2011. New recommendations include an increased dose of ceftriaxone with adjuvant use of azithromycin, as well as test of cure (TOC) in all cases. We present an audit of adherence to new antibiotic prescribing guidelines as well as TOC uptake in an inner city genitourinary medicine clinic. Among the 271 (242 male, 29 female) patients included, 96% ( n = 260) received the new first-line treatment. Test of cure uptake was found to be suboptimal at 55% ( n = 149) with the majority (67%) of these taking place within 20 days of treatment. The new first-line treatment for gonorrhoea is feasible and generally accepted by patients. However the TOC uptake is low, emphasising the need for robust follow-up and recall policies. Further study is required into the optimal timing for TOC.